Progress in domestication research: Explaining expanded empirical observations. (15th November 2022) - Fuller, Dorian Q.; Denham, Tim; Kistler, Logan; Stevens, Chris; Larson, Greger; Bogaard, Amy; Allaby, Robin
Abstract: Abbo and Gopher contend that we offer nothing new to the study of domestication in three recent papers (Bogaard et al., 2021; Allaby et al., 2021, Allaby et al., 2022b). They claim that we offer no "innovation, a new venue of research" and "use a new jargon to express old ideas." They further claim as erroneous our key conclusions about domestication as: protracted, co-evolutionary, comprising multiple pathways of convergent evolution, and taking place at the landscape scale. Here we defend these recent contributions as genuine progress that builds on previous ideas and hypotheses through empirical illustration and a raft of new data. Combining new data with old and new theory, we develop frameworks that suggest future directions for research.